Job satisfaction and individual happiness among employees at a public higher education institution / Siti Rosnita Sakarji …[et al.] - Sakarji, Siti Rosnita; Wan Azib, Wan Nor Hazimah; Luqman, Azyanee; Mohd Pauzi, Nooradzlina; Shari, Asma Shazwani; Ismail, Hadhifah Fadhlina; Abdullah Thani, Ayu Kamareenna; Nik Min, Nik Mohd Faris; Haidar Ishak, Muhammad Ammar; Mohd Yusri, Nur Alyaa Athirah (UiTM Press, 2021)
Employees are the most important asset of organisations. Making them happy with their workplace and the work itself will benefit not only the employees but also the organisations. Employee satisfaction is also based on their awareness of future development. Hence, this paper aims to determine the relationship between job satisfaction and five variables of pay, colleagues, management, nature of work and promotion toward individual happiness. Data were collected from 126 respondents from Universiti Teknikal Malaysia Melaka (UTeM), a public higher education institution in Malaysia using simple random sampling. Subsequently, the data were derived using SPSS Version 22.0. The findings indicated that there is a positive relationship between pay, colleague, management, nature of work, and promotion. Based on the results, the nature of work and promotion are the most important factors that influence employee happiness, thus leading to job satisfaction. Moreover, the result from the hypothesis test revealed that there is a significant relationship between pay, colleagues, management, nature of work, and promotion. These findings may guide the implementation of policies by human resources or other organisation management in a higher education institution. For instance, they may use job happiness (mental well-being) as a predictor of employee behaviours and then formulate recruitment policies that will help maintain employee happiness and satisfaction, thereby helping in employee retention.